PENGARUH RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM - Furniawan Furniawan; Fitri Rosdianti (The Asia Pacific Journal Of Management Studies, 2020)
The alternative used in investing by investors is stocks, because the profits obtained are greater so that the funds needed by investors to invest are less than bonds. The purpose of this study was to determine the simultaneous effect of Return On Equity and Debt to Equity Ratio on stock prices.This study uses a quantitative method with a descriptive approach, the population included in this study are companies that are included in the food and beverage sector index, namely companies that have been considered to have accountable performance and meet the performance required by the Indonesia Stock Exchange. covering the food and beverage sector. So that only 9 companies for 4 periods.Return On Equity has a significant effect on stock prices. Debt To Equity Ratio does not have a significant effect on stock prices. it can be concluded that the variable Return On Equity (X1), Debt To Equity Ratio (X2) has a significant effect on Stock Price (Y).